2010
DOI: 10.1002/lary.20797
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of mesenchymal stem cells from human vocal fold fibroblasts

Abstract: Objective/Hypothesis Mesenchymal stem cells (MSCs) originally isolated from bone marrow, are fibroblast-looking cells that are now assumed to be present in the stromal component of many tissues. MSCs are characterized by a certain set of criteria including their growth culture characteristics, a combination of cell surface markers, and the ability to differentiate along multiple mesenchymal tissue lineages. We hypothesized that human vocal fold fibroblasts (hVFF) isolated from the lamina propria meet the crite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
71
0
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 72 publications
(78 citation statements)
references
References 16 publications
4
71
0
3
Order By: Relevance
“…6,7 MSCs are a suitable alternative to primary vocal fold fibroblasts (VFFs) for vocal fold tissue engineering, considering their similar phenotype, multipotency, and immunoregulatory functions. 6,8 Mounting evidence confirms the regulatory role of the tissue-specific microenvironment in controlling the behaviors of MSCs.…”
Section: Introductionmentioning
confidence: 87%
“…6,7 MSCs are a suitable alternative to primary vocal fold fibroblasts (VFFs) for vocal fold tissue engineering, considering their similar phenotype, multipotency, and immunoregulatory functions. 6,8 Mounting evidence confirms the regulatory role of the tissue-specific microenvironment in controlling the behaviors of MSCs.…”
Section: Introductionmentioning
confidence: 87%
“…7,23 BM-and AT-MSCs were cultured in a 37°C incubator with 5% CO 2 -95% humidified atmosphere with standard media (alpha minimum essential media supplemented with 10% fetal bovine serum [FBS-Hyclone, Logan, UT], 1 · nonessential amino acids [NEAA, Sigma Aldrich], and 4 mM Lglutamine [Sigma Inc.], 100 U/mL penicillin, and 0.01 mg/ mL streptomycin sulfate [Sigma Inc.]). VF-MSCs were cultured in Dulbecco's modified essential medium with 10% FBS, 100 U/mL penicillin, 0.01 mg/mL streptomycin sulfate, and 1 · NEAA (all from Sigma Inc.).…”
Section: Human Msc Isolationmentioning
confidence: 99%
“…[3][4][5] These progenitor cells isolated from different tissue sources all have the capability to differentiate into multiple cell lineages (such as bone, fat, and cartilage), and have specific cell surface marker characteristics, [6][7][8] though there is evidence to suggest that these cells can have phenotypical differences based on their tissue source of origin. 9 Most recently, unique immunomodulatory properties of MSCs, such as their potential use across HLA barriers, have been an area of active investigation as such properties make them of much more value in regenerative medicine.…”
mentioning
confidence: 99%
“…11 Moreover, studies have shown that primary vocal fold fibroblasts (PVFFs) and MSCs share similar cell surface markers, immunophenotypic characteristics, and differentiation potential. 12 Thus, MSCs are a suitable alternative to PVFFs for vocal fold tissue engineering. MSCs are naturally sensitive to their environment, and each tissue contains a unique stem cell niche that fosters the tissuespecific stem cell differentiation and tissue development.…”
Section: Introductionmentioning
confidence: 99%